Photoluminescence Lifetime Based Investigations of Linker Mediated Electronic Connectivity Between Substrate and Nanoparticle - Miethe, Jan F.; Lübkemann, Franziska; Bigall, Nadja C.; Dorfs, Dirk (Frontiers in Chemistry, 2019)
The evolution of systems based on nanoparticles as the main component seems to be a self-accelerating process during the last five decades. Hence, an overview across this field gets more and more challenging. It is sometimes rewarding to focus on the fundamental physical phenomenon of the electronic interconnection between the different building blocks of the obtained devices. Therefore, the investigation of charge transport among the utilized particles and their substrate is one of the mandatory steps in the development of semiconductor nanoparticle based devices like e.g. sensors and LEDs. The investigation of the influence of tunneling barriers on the properties of nanoparticle-functionalized surfaces is a challenging task. The different basic influences on the charge transport dynamics are often difficult to separate from each other. Non-invasive and easily viable experiments are still required to resolve the charge distributing mechanisms in the systems. In the presented work, we want to focus on thin and transparent indium tin oxide (ITO) layers covered glass slides since this substrate is frequently utilized in nanoelectronics. CdSe/CdS nanorods (NRs) are applied as an optically addressable probe for the electronic surface states of the conductive glass. The presented experimental design provides the prove of electronic interconnections in ITO coated glass/linker/NR electrodes via easy reproducible functionalization and polishing experiments. UV/Vis absorption and photoluminescence (PL) lifetime measurements revealed changes in the optical properties caused by differences in the charge carrier dynamics between the systems... Our work is focused on the modification of charge carrier dynamics due to the application of linker molecules with different functional groups like (3-mercaptopropyl)methoxysilane (MPTMS) and (3-aminopropyl)trimethoxysilane (APTMS). The presented observations are explained with a simple kinetic model.